Institutional Governance of Education: An Analysis of Higher Education and Madrasah Accreditation Policies in Mataram City and West Lombok - Raihan, Ahyar, Saparudin (Journal of Educational Studies, 2025)
Educational accreditation occupies a pivotal role within national quality assurance systems; however, its effectiveness in driving substantive institutional governance transformation remains subject to critical scholarly debate. This study analyses how accreditation policy shapes institutional governance patterns in private higher education institutions and madrasah in Mataram City, specifically Universitas Muhammadiyah Mataram (UMMAT) and Universitas Nahdlatul Ulama NTB (UNU NTB) as private university representatives, and Madrasah Aliyah Swasta Nurul Hakim and Madrasah Aliyah Swasta Darul Aminin as madrasah representatives. Employing a qualitative multiple case study approach across 24 informants, analyzed through reflexive thematic analysis assisted by NVivo 15, the study identifies five core themes: administrative governance, institutional quality culture, policy implementation, ceremonial isomorphism, and human financial capacity. Key findings reveal that accreditation predominantly functions as a formal legitimacy mechanism rather than a substantive driver of quality; governance dualism between BAN PT and BAN PDM produces policy incoherence that structurally disadvantages private madrasah; and ceremonial isomorphism is considerably more pronounced in madrasah settings. The study recommends inter-ministerial regulatory harmonization, capacity-differentiated accreditation instruments, and performance-based financing for private madrasah